Behaviours of adolescents towards safety measures at school and in traffic and their health beliefs for injuries - GÜR, KAMER (WILEY, 2020)
Aim The aim of this work is to determine the behaviours of adolescents towards safety measures at school and in traffic and their health beliefs for injuries. Background Adolescents are more prone to injuries, as they are more willing to try risky health behaviours. Methods This descriptive and cross-sectional study was conducted at high schools in Turkey. The data were collected from high school students based on the self-report method between October 2017 and January 2018. Frequency, percentage, chi-square,ttest, and logistic regression were used to analyse the data. Results A total of 481 adolescents participated in the study. The response rate is 96.05%. As a result of the research, 12.5% of the adolescents reported that they were injured in traffic and 18.9% of them were injured at school. Adolescents who did not have an accident had higher scores of health beliefs than those who had an accident (p< 0.05). The most important predictors of injury are being male (OR: 2.52, 95% CI [1.19, 53.00]), parents' separation (OR: 2.82, 95% CI [0.98, 8.09]), and not believing that traffic rules were safe (OR: 3.15, 95% CI [1.42, 6.97]). Conclusion Adolescents have risky behaviours at school and in traffic, and these risk behaviours are related to demographic characteristics and health beliefs. School nurses should plan health belief model-based injury prevention programs.
Keywords: adolescence; health belief; nursing; risky health behaviours; school and traffic injuries; UNINTENTIONAL INJURIES